Perubahan Sosial Masyarakat: Studi Kasus Pola Konsumerisme Pengguna Media Sosial Twitter Pada Event Tanggal Kembar Shopee - Anita Andriana; Ziyan Nahry Abidah; Rizki Monica Rahmadhani (LPPM Politeknik Pratama, 2024)
Social change in society underwent a major transformation, especially in the economic field. The emergence of e-commerce is an impact of social changes in the economic field. Shopee is one of the e-commerce that has several promos and events every month, such as price discounts, vouchers, flash sales, cashback, free shipping, big sales, payday party, and peak day event. This study aims to describe the consumerism patterns of Twitter social media users in responding to and engaging the Shopee peak day event, as well as to understand the factors and influences of the event on the overall consumerism pattern. Through a qualitative approach using the case study method, this study was conducted by observing the consumerism pattern of Twitter social media users. The data collection method was carried out by virtually observing the interaction of Twitter social media users during the Shopee peak day event. The results of this study indicate that there are social changes regarding consumption patterns among Twitter social media users at the Shopee peak day event. In line with the theory of consumer behavior by Alfred Marshall, changes in public consumption patterns of Twitter social media users increased at the Shopee peak day event which was centered on the need to be consumptive.